Anaphylaxis in Latin America: a report of the online Latin American survey on anaphylaxis (OLASA). (2011)
Of all patients, 68.5% were older than 18 years, 41.6% were male, and 65.4% experienced the allergic reaction at home. The etiologic agent was identified in 87.4% of cases and predominantly consisted of drugs (31.2%), foods (23.3%), and insect stings (14.9%). The main symptom categories observed during the acute episodes were cutaneous (94.0%) and respiratory (79.0%). The majority of patients (71.6%) were treated initially by a physician (office/emergency room) within the first hour after the reaction occurred (60.2%), and 43.5% recovered in the first hour after treatment. Most patients were treated in an emergency setting, but only 37.3% received parenteral epinephrine alone or associated with other medication. However, 80.5% and 70.2% were treated with corticosteroids or antihistamines (alone or in association), respectively. A total of 12.9% of the patients underwent reanimation maneuvers, and 15.2% were hospitalized. Only 5.8% of the patients returned to the emergency room after discharge, with 21.7% returning in the first 6 hours after initial treatment.